VOCATIONAL AND SKILL-BASED EDUCATION IN INDIA: A CRITICAL REVIEW OF NEP 2020’S IMPLEMENTATION AND CHALLENGES. - Aadil Hussain Mir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The National Education Policy (NEP) 2020 marks a transformative shift in India's education system by integrating vocational and skill-based education at all levels. This paper critically examines the implementation, challenges, and potential impacts of vocational education under NEP 2020. The policy aims to bridge the gap between formal education and employability by incorporating practical training, industry partnerships, and skill development programs from an early stage. A key highlight of the policy is the introduction of vocational education from Grade 6 onwards, allowing students to gain hands-on experience through internships and apprenticeships. The paper analyzes how this shift aligns with global best practices and examines its potential to enhance India’s workforce competitiveness. It further explores policy challenges, including teacher training, infrastructure requirements, and integration with mainstream education. Additionally, this study delves into the role of technology, digital learning platforms, and public-private partnerships in ensuring the successful implementation of vocational education. The paper concludes with policy recommendations to strengthen vocational education under NEP 2020, ensuring it meets the dynamic demands of the 21st-century job market while fostering an entrepreneurial mindset among students.